2021
DOI: 10.1108/itp-08-2020-0580
|View full text |Cite
|
Sign up to set email alerts
|

Attention and behaviour on fashion retail websites: an eye-tracking study

Abstract: PurposeThe purpose of this paper is to identify attention, cognitive and affective responses towards a fashion retailer's website and the behavioural outcomes when shopping online.Design/methodology/approach52 eye-tracking tests and 52 qualitative semi-structured interviews were conducted.FindingsConsumer attention and behaviour differ across web pages throughout the shopping journey depending on its content, function and consumers' goal. Top-down attention is more dominant than bottom-up attention when consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
0
17
0
1
Order By: Relevance
“…For example, by means of text mining, Ghose and Ipeirotiss (2010) concluded that the use of product reviews is influenced by textual features, such as subjectivity, informality, readability, and linguistic accuracy. Likewise, Boardman and Mccormick (2021) found that consumer attention and behavior differ across web pages throughout the shopping journey depending on its content, function, and consumer’s goal. Furthermore, Guo et al (2020) showed that pleasant online customer reviews lead to a higher purchase likelihood compared to unpleasant ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, by means of text mining, Ghose and Ipeirotiss (2010) concluded that the use of product reviews is influenced by textual features, such as subjectivity, informality, readability, and linguistic accuracy. Likewise, Boardman and Mccormick (2021) found that consumer attention and behavior differ across web pages throughout the shopping journey depending on its content, function, and consumer’s goal. Furthermore, Guo et al (2020) showed that pleasant online customer reviews lead to a higher purchase likelihood compared to unpleasant ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is not difficult to provide high-quality and interactive visual information on product detail pages, which is considered to be beneficial to the emotional experience of consumers. However, product list pages are the most frequently visited by consumers and spend the most time on them (Boardman and Mccormick, 2021), yet the product pictures are much smaller. Take the online clothing product list page of the Amazon e-platform as an example.…”
Section: Consumers' Visual Attention and Emotional Experiencementioning
confidence: 99%
“…To reduce bias and enhance the reliability of the data, detailed records of the research process were maintained. The researchers conducted multiple coding cycles (Boardman and McCormick, 2021), which involved each of the four research members individually coding the data initially. Then, each theme and sub-theme that emerged for each researcher were discussed, compared and corroborated to enhance transparency and reflexivity, adhering to Lipson et al (2020).…”
Section: Discussionmentioning
confidence: 99%